Development of length expansion temperature detector based on arduino uno. Issue 1 (1st January 2022) - Azhar; Siswadi; Doyan, A; Susilawati; Taufik, M; Hudha, L S
Abstract: Length expansion is an increase in the length of an object due to receiving heat. If a solid object is heated then the object will expand in all directions, in other words the length increases the length of an object because it receives heat. A tool for comparing the length expansion of various metals is the Musschenbrock. To measure the temperature of an object can use a sensor. The sensor used in this research is the LM 35 based on Arduino Uno. The development method for this Length expansion tool temperature detector starts from tool design, hardware design, software design, tool calibration and tool testing. From the results of research using an Arduino Uno-based temperature detector, it can be said that this research was successful because the values obtained were almost the same as the existing theory. So, this detector is suitable for use in laboratories or schools as a learning medium to determine the length expansion of metals.